Halogenated Bis(methoxybenzylidene)‐4‐piperidone Curcuminoids with Improved Anticancer Activity. (23rd April 2018) - Schmitt, Florian; Subramaniam, Dharmalingam; Anant, Shrikant; Padhye, Subhash; Begemann, Gerrit; Schobert, Rainer; Biersack, Bernhard
Abstract: A series of readily available curcuminoids with a halogenated bis(4‐methoxy/4, 5‐dimethoxybenzylidene)‐4‐piperidone structure were prepared and analyzed for their cytotoxic impact on eight human cancer cell lines of five different entities. The known 3, 4, 5‐trimethoxybenzylidene curcuminoid2 a and the new bis‐(3‐bromophenyl) and bis‐(3, 5‐dibromophenyl) derivatives3 c and3 d proved to be more strongly antiproliferative than the known curcuminoid EF24 against six of these cell lines. Compounds2 a and3 c caused a distinct increase of reactive oxygen species, which eventually elicited apoptosis in 518A2 melanoma cells. Compound2 a arrested 518A2 melanoma cells in G1 phase of the cell cycle and had no effect on the expression of pro‐metastatic matrix metalloproteinases MMP‐2 and MMP‐9, whereas3 c led to an accumulation of 518A2 cells in the G2 /M phase and to a downregulation of MMP‐2 expression. In addition, treatment with2 a and3 c resulted in significant inhibition of colony formation in HCT116 cells. Both2 a and3 c showed antiangiogenic activity, for example, by inhibiting the formation of sub‐intestinal veins (SIV) in zebrafish embryos. Compound3 c was also well tolerated by mice and inhibited the growth of HCT116 colon cancer xenografts. Abstract : The curcumin halo effect : The new 3‐bromo‐4, 5‐dimethoxyphenyl curcuminoid3 c showed higher antiproliferative activity than the known fluoro‐curcuminoid EF24. Compound3 c revealed great potential as an anticancer drug candidate due to its superior antiproliferative, ROS‐inducing, and anti‐invasive activity as well as its strong tumor growth inhibitory activity in HCT116 mouse xenografts.